ChatGPT: Education Reimagined - Crompton, Helen (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2024)
The keynote presentation explained the profound impact of ChatGPT on the educational landscape. The presentation started by providing an understanding of what ChatGPT is and how to use this artificial intelligence tool. This described how unlike typical search engine searches on a topic, such as Google search, which provides website that may have the answer to what you are looking for, ChatGPT provides you the answer directly. An overview of ChatGPT highlighted how the data which ChatGPT provides responses with is from Microsoft Bing search engine content. A review of the limitations and misuses of ChatGPT are explained with strategic guidance on how to mitigate these challenges. These topic include how students can use ChatGPT to cheat by having the program do the work for them. The program can be prone to inaccuracies and hallucinations, where the answers are incorrect but presented in a way that makes it appear correct. Plagiarism is an issue with ChatGPT gathering content from the Internet and some of which is copyrighted. ChatGPT also exhibits bias which may probably be connected with the data used in the development of the tool. Students must also be reminded that they should not include personal data when conversing with the tool. Then, the presentation then moved from the negative aspects of the tool to highlight the numerous affordances of ChatGPT and its transformative capabilities in the realm of education. By leveraging ChatGPT, educators have the unique opportunity to foster a more inclusive, personalized, and impactful educational experience. Practical insights and innovative approaches were presented that harness the full potential of ChatGPT, enabling educators to create a learning environment that caters to the diverse needs of your students.